A simplified hardness model for WC-Co-Cubic cemented carbides - Pang M.; Du Y.; Zhang W.-B.; Peng Y.-B.; Zhou P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Hardness is an essential mechanical indication of cemented carbides. The current work presents an approach to predict the hardness of three-phase WC–Co–Cubic cemented carbides, which establishes a relationship among composition, structure and mechanical performance. With the input of initial composition and grain sizes of carbides, structural parameters needed to predict the hardness can be calculated by thermodynamic calculations and diffusion simulations. The calculated hardness of a series of WC–Co–Cubic cemented carbides agrees reasonably with the experimental data. The present model is of reference to predict the hardness for multi-phase composites and design the new type of WC–Co-based cemented carbides.